Pengaruh E-Learning Sebagai Media Pembelajaran Terhadap Keaktifan Mahasiswa Tingkat Dua Pendidikan Ekonomi UN PGRI Kediri Selama Masa Pandemi Coronavirus Disease (Covid-19) - Baskarayudha S. , Moh. Alfarizi; Alfiyah, Binti; Setiawan, Sendi; Afandi, Tjetjep Yusuf (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The use of instructional media in the teaching and learning process is an effort to increase the effectiveness and quality of the learning process which in turn can improve the quality of student learning outcomes. The use of instructional media in the teaching and learning process has several benefits. The form of information technology that can be used as a learning medium is to use e-learning. E-learning is an innovation that will be used in learning, not only for learning materials but also changes in various student competencies. E-learning is to support the implementation of the learning process, it is hoped that it can increase the absorption of school fees for the material provided, increase active participation from school fees, increase the ability of schools to learn independently, materials improve the quality of education and training, increase the ability to display information with information technology devices , expanding the teaching and learning process using the internet, not only limited to time and space. The form of information technology that can be used as a learning medium is called e-learning. E-learning is an innovation that can be used in the learning process, not only for learning material but also for changes in various student competencies. Through e-learning, students not only listen to discussion material from educators but are also active in observing, conducting, demos, and so on. Learning materials can be virtualized in various formats so that they can be more interesting and more dynamic to motivate students in learning.